Assistance and Improvement of Locomotor, Non-Locomotor and Manipulative Movement Skills for Elementary School Students in the Karang Taruna Region, Muara Gembong District By Using Rapid Motion Media (GeCe) during the Covid 19 - Juli Candra; Faridatul Ala; Desy Tya Maya Ningrum (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Lecturers of the Sports Coaching Education Study Program in collaboration with the Youth Organization of Muara Gembong District conducted Community Service activities to arouse children's interest to be even more enthusiastic in carrying out sports activities. PKM activities are carried out using GeCe (Fast Motion) media. Community service activities using socialization and training methods for 8 meetings with the duration of implementation, 2 meetings for the initial test and final test and 6 meetings for basic movement improvement activities. Based on the results of the initial test results for locomotor, non-locomotor and manipulative movements of elementary school students, the results of the 30M running speed test with an average of 78% and the initial test results for the agility ability of the Illinois agility test with an average of 71.56% then after PKM activities were carried out then the results of the second test obtained speed test results with an average of 84% and agility test results with an average of 82.22%. From the final results, PKM activities can improve locomotor, non-locomotor and manipulative movement abilities in elementary school students in the Karang Taruna area, Muara Gembong District.